2015
DOI: 10.1189/jlb.5a0814-413r
|View full text |Cite
|
Sign up to set email alerts
|

Combined PI3K/Akt and Hsp90 targeting synergistically suppresses essential functions of alloreactive T cells and increases Tregs

Abstract: Acute graft-versus-host disease is still a major cause of transplant-related mortality after allogeneic stem cell transplantation. It requires immunosuppressive treatments that broadly abrogate T cell responses, including beneficial ones directed against tumor cells or infective pathogens. Inhibition of the heat shock protein of 90 kDa has been demonstrated to eliminate tumor cells, as well as alloreactive T cells while preserving antiviral T cell immunity. Here, we show that the suppressive effects of heat sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Indeed, this drug inhibits the phosphorylation of ERK 1/2 and AKT and blocks the Notch signaling pathway in different cell lines (Huang et al, 2016;Liang et al, 2015;Wieland et al, 2013). All of these pathways are involved in the physiopathology of GVHD (Allen et al, 2012;Berges et al, 2015;Lu et al, 2008;Zhang et al, 2011). In our hands, we observed an abrogation of the activation of these three pathways along with the improvement of the disease.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, this drug inhibits the phosphorylation of ERK 1/2 and AKT and blocks the Notch signaling pathway in different cell lines (Huang et al, 2016;Liang et al, 2015;Wieland et al, 2013). All of these pathways are involved in the physiopathology of GVHD (Allen et al, 2012;Berges et al, 2015;Lu et al, 2008;Zhang et al, 2011). In our hands, we observed an abrogation of the activation of these three pathways along with the improvement of the disease.…”
Section: Discussionsupporting
confidence: 53%
“…1 T cells, 45,58 allowing preservation of antiviral immunity. Recent studies have suggested that Hsp90 inhibition using 17-AAG-protected intestine paneth cells against alloreactive T-cell-mediated injury, leading to improved epithelium regeneration and reduction of damage to the gastrointestinal track.…”
mentioning
confidence: 99%
“…As is known, the Akt/mTOR pathways have been reported to play prominent roles in T cell proliferation, T cell activation, migration, cytokine production and pathogenicity in the induction of aGVHD [ 31 , 32 ]. S1PR1 has been shown to be important in inflammatory responses in immune cells, the decreased expression of S1PR1 can attenuate aGVHD in mouse model [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, active Akt/mTOR signaling suppresses the function of Tregs and significantly impairs expression of Foxp3 [ 69 , 70 ]. Inhibiting AKT can attenuate aGVHD and increase Tregs [ 31 ]. Our and other group also found that active Akt signaling can aggravate the pathogenesis of aGVHD and reduce the proportion of Tregs [ 6 , 71 ].…”
Section: Discussionmentioning
confidence: 99%